Peran Guru dalam Menumbuhkan Karakteristik Wirausaha pada Siswa SMK Melalui Pembelajaran Kewirausahaan - Tahir, Sumiati; Tahir, Thamrin; Tahir, Muhammad Ilyas Thamrin; Syam, Agus; Haruna, Hasisa (CV. Era Digital Nusantara, 2025)
This study aims to analyze the role of teachers in fostering entrepreneurial characteristics among Vocational High School (SMK) students through entrepreneurship learning. The background of this study lies in the high unemployment rate among SMK graduates, indicating a gap between vocational education objectives and labor market demands. A qualitative descriptive approach was employed, with data collected through in-depth interviews, classroom observations, and documentation, then analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings reveal that teachers play strategic roles in three main dimensions: motivators, facilitators, and role models. As motivators, teachers inspire entrepreneurial interest through motivational stories and direct encouragement. As facilitators, they provide experiential learning such as project-based learning and small business simulations. As role models, teachers with real business experience act as authentic examples for students. However, the study also identifies structural challenges, including limited practice facilities, low parental support, and weak collaboration with industry. The results highlight that entrepreneurship education should not only focus on cognitive knowledge but also emphasize attitudes, values, and entrepreneurial skills. Practically, this study recommends stronger collaboration between schools, government, parents, and industry to reinforce the entrepreneurship education ecosystem in vocational schools.